2011
DOI: 10.1111/j.1538-7836.2010.04134.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of von Willebrand factor in the etiologic subtypes of ischemic stroke

Abstract: Summary. Background: Compared with coronary artery disease, there are few studies on von Willebrand factor (VWF) in ischemic stroke (IS). Moreover, there is little information on VWF in the etiologic subtypes of IS. Objectives: The aim of the present study was to investigate VWF in IS and in the etiologic subtypes of IS. Patients/methods: The Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS) is a case-control study comprising 600 patients and 600 matched controls. Etiologic IS subtype was defined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 29 publications
4
51
1
5
Order By: Relevance
“…18 In the prospective Rotterdam Study, the risk of ischemic stroke increased with rising levels of VWF in plasma, 19 and in the case-control SAHLSIS Study, VWF levels were found to be increased in ischemic stroke, both in the acute phase and 3 months after the event. 20 The inhibition of the GPIb-IX-V-vWF interaction may theoretically prevent pathologic thrombosis but may not have much influence on physiologic hemostasis, given the preeminent role of GPIb-VWF in platelet activation under high shear conditions 21 and may thus represent a particularly promising target for the treatment of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…18 In the prospective Rotterdam Study, the risk of ischemic stroke increased with rising levels of VWF in plasma, 19 and in the case-control SAHLSIS Study, VWF levels were found to be increased in ischemic stroke, both in the acute phase and 3 months after the event. 20 The inhibition of the GPIb-IX-V-vWF interaction may theoretically prevent pathologic thrombosis but may not have much influence on physiologic hemostasis, given the preeminent role of GPIb-VWF in platelet activation under high shear conditions 21 and may thus represent a particularly promising target for the treatment of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…4 The von Willebrand factor (vWF) is synthesized primarily by vascular endothelial cells and promotes platelet adhesion and aggregation, leading to thrombus formation. 1 Increased levels of vWF in stroke patients have been reported in several case-control studies, [5][6][7][8] but prospective studies have been inconsistent, with some showing a positive relationship 9,10 and others showing no relationship [11][12][13][14] between vWF and stroke risk. Fibrin D-dimer is the primary degradation product of cross-linked fibrin and is a marker of activated coagulation and fibrinolysis.…”
mentioning
confidence: 99%
“…This result was in agreement with the other researchers. 2,12,13 The mechanism responsible for increase plasma vWF levels and the occurrence of ischemic stroke is due to inflammation resulting in endothelial cell activation, which leads to increase vWF secretion and subsequent reduce clearance of it. When vWF more release, it facilitates over platelet adhesion leading to secretion of excess active substances and excess generation of platelet plug which leading to thrombosis.…”
Section: -Group I (Control Group)mentioning
confidence: 99%
“…When vWF more release, it facilitates over platelet adhesion leading to secretion of excess active substances and excess generation of platelet plug which leading to thrombosis. [12][13][14] It has long been known that lipids abnormalities are a major risk factor for the onset of ischemic stroke. 15 Our data reveal that the mean fasting serum T.Ch level in patients with ischemic stroke was significantly higher (P <0.01) than the control group.…”
Section: -Group I (Control Group)mentioning
confidence: 99%